The Effects of Profitability, Capital Intensity, and Leverage on Tax Avoidance on Companies in the Jakarta Islamic Index - Ridwansyah; Any Eliza; Safira, Marini Rahma (International Journal of Economics (IJEC), 2023)
The purpose of this study was to investigate potential correlations between tax evasion and leverage, capital intensity, and profitability. This investigation's primary goals and focus are companies that are listed in the Jakarta Islamic Index for the 2019–2021 period. 54 observation samples in all were used in this study, and they were all chosen using purposive sampling methods. The data examined using Eviews software was subjected to multiple linear regression testing methodology for the purposes of this investigation. The use of leverage and tax evasion are unrelated, according to study findings. Tax evasion is impacted by both capital intensity and profitability considerations.